Respuestas

2013-05-08T04:48:24+02:00

Si:

a_n = a_k + (n-k)(d)
a_n = 42 + (n-12)(2)
a_n = 42 +2n -24
a_n = 2n + 18

a_12 = 2(12) + 18= 24 + 18 = 42
a_1 = 2(1)+18 = 2 + 18 = 20

 

2013-05-08T07:37:54+02:00
Esta mal el planteamiento anterior pero bien la respuesta..

an = ultimo termino = 42
a1 = primer termino = ?
r = razon =2
n = numero de terminos = 12

an = a1 + ( n -1 ) *r
42 = a1 + ( 12 - 1 ) * 2
42 = a1 + 22
a1 = 42 - 22
a1 = 20
primer termino = 20

creo que asi es menos complicado..
saludos